Piezoelectric Accelerometers with Integral Electronics - Levinzon, Felix (Springer International Publishing : Imprint: Springer, 2015)
This book provides an invaluable reference to Piezoelectric Accelerometers with Integral Electronics (IEPE). It describes the design and performance parameters of IEPE accelerometers and their key elements, PE transducers and FET-input amplifiers. Coverage includes recently designed, low-noise and high temperature IEPE accelerometers. Readers will benefit from the detailed noise analysis of the IEPE accelerometer, which enables estimation of its noise floor and noise limits. Other topics  useful for designers of low-noise, high temperature silicon-based electronics include noise analysis of FET amplifiers, experimental investigation and comparison of low-frequency noise in different JFETs and MOSFETs, and ultra-low-noise JFETs (at level of 0.6 nV/√Hz). The discussion also includes ultra-low-noise (at level of 3 ng/√Hz) seismic IEPE accelerometers and high temperature (up to 175 ̊C) triaxial and single axis miniature IEPE accelerometers, along with key factors for their design. • Provides a comprehensive reference to the design and performance of IEPE accelerometers, including low-noise and high temperature IEPE sensors; • Includes noise analysis of the IEPE accelerometer, which enables estimation of the its noise floor and noise limits; • Describes recently design of ultra-low-noise (at level of 3 ng/√Hz) IEPE seismic accelerometers and high temperature (up to 175 ̊C) triaxial and single axis miniature IEPE accelerometers; • Compares low-frequency noise in different JFETs and MOSFETs including measurement results of ultra-low-noise (at level of 0.6 nV/√Hz) JFET; • Presents key factors for design of low-noise and high temperature IEPE accelerometer and their electronics.